2012
DOI: 10.1016/j.bone.2012.08.130
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with anti-osteoporosis medication use: Data from the Global Longitudinal Study of Osteoporosis in Women (GLOW) USA cohort

Abstract: Introduction Many women at risk of fracture do not receive anti-osteoporosis medication (AOM), while others may be receiving unnecessary treatment. Purpose To examine the characteristics associated with AOM use among women at low and high risk of fracture. Methods The Global Longitudinal Study of Osteoporosis in Women (GLOW) is a prospective cohort study in which data were collected, via self-administered questionnaires, from 60,393 non-institutionalized women aged ≥55 years in 10 countries between October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Other strengths of this study included the large sample size and the representative sample because of the unique sampling method in the GLOW . The participants were recruited according to the lists provided by the physician practices with few exclusion criteria, which thus would lead to the women being nonselected and representative of the practices in real world …”
Section: Discussionmentioning
confidence: 99%
“…Other strengths of this study included the large sample size and the representative sample because of the unique sampling method in the GLOW . The participants were recruited according to the lists provided by the physician practices with few exclusion criteria, which thus would lead to the women being nonselected and representative of the practices in real world …”
Section: Discussionmentioning
confidence: 99%
“…Despite a number of advances, particularly in the diagnosis of osteoporosis, the assessment of fracture risk, the development of interventions that reduce the risk of fractures, and the production of practice guidelines, many surveys indicate that a minority of men and women at high fracture risk actually receive treatment . In patients who sustain a fragility fracture, fewer than 20% of individuals receive therapies to reduce the risk of future fracture within the year following the fracture .…”
mentioning
confidence: 99%
“…(5)(6)(7) Despite a number of advances, particularly in the diagnosis of osteoporosis, the assessment of fracture risk, the development of interventions that reduce the risk of fractures, and the production of practice guidelines, many surveys indicate that a minority of men and women at high fracture risk actually receive treatment. (8)(9)(10)(11)(12)(13)(14) In patients who sustain a fragility fracture, fewer than 20% of individuals receive therapies to reduce the risk of future fracture within the year following the fracture. (11,12,(15)(16)(17)(18) Paradoxically, the therapeutic care gap may be particularly wide in the elderly in whom the importance and impact of treatment is high; studies have shown that as few as 10% of older women with fragility fractures receive any osteoporosis therapy (estrogens not considered).…”
mentioning
confidence: 99%
“…Common barriers to treatment initiation include: concerns over side effects 21 including gastro-intestinal (GI) events [22][23][24][25] , cost 26 , and patient frailty 26 . While some previous studies have attempted to identify characteristics associated with the likelihood of OP treatment [8][9][10]19 , most published studies have focused on treatment among patients newly indicated for treatment and did not include patients with prior use of therapy, even though prior osteoporosis therapy has been shown to be predictive of future treatment 27 . Additionally, few studies of OP nontreatment focus on a Medicare population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that non-treatment of osteoporosis is common [8][9][10][11][12][13][14][15][16][17][18][19][20] , whether assessed after clinical or self-reported OP diagnosis 10,20 , before OP-related fractures 8,11,16 , or after fractures 9,[11][12][13][14][15][16][17][18][19] . Common barriers to treatment initiation include: concerns over side effects 21 including gastro-intestinal (GI) events [22][23][24][25] , cost 26 , and patient frailty 26 .…”
Section: Introductionmentioning
confidence: 99%